Anthropometric Characteristics of Young Turkish Male Athletes - Pelin, Can (Array, 2009)
Comparative reports on the anthropometric characteristics of athletes are certainly important in modern sports and have long been studied by sports scientists. Studies on Turkish athletes however, are limited. In the present study physical characteristics of athletes active in various sports (American football, basketball, volleyball and football) were observed and compared to each other and to those of non-athlete individuals. 153 volunteer male subjects participated in the study. All of the athletes were licensed members of teams in inter-university leagues.